Two case reports of B-cell lymphopenia associated with IGLL1 variants identified through newborn screening in Ukraine - Boyarchuk, Oksana; Romanyshyn, Yaryna; Savchak, Ihor; Kravets, Volodymyr; Shymanska, Ivanna; Makukh, Halyna (Frontiers in Pediatrics, 2025)
Before the implementation of newborn screening (NBS), only a few cases of agammaglobulinemia associated with IGLL1 variants had been reported. The IGLL1 gene encodes the surrogate light chain components λ5 and VpreB, which form a crucial part of the pre-B cell receptor complex. A recently published study reported 17 cases of agammaglobulinemia caused by IGLL1 variants, the vast majority of which were identified through NBS. Here, we report two cases of B-cell lymphopenia along with IGLL1 variants identified through NBS in Ukraine. Both neonates had undetectable KREC and normal TREC levels at birth. Despite the presence of B-cell lymphopenia, only one patient exhibited a transient decline in IgG levels. IgA and IgM levels remained normal during the first year of follow-up, which had not been reported in previous IGLL1 cases. Both children presented with mild upper respiratory tract infections. Genetic analysis revealed that both patients carried the c.425C > T variant, with one patient also harboring the c.258del variant. These variants have been linked to B-cell lymphopenia and low KREC levels in prior studies. Two additional variants were identified on the second chromosome: c.368C > G, which is predicted to be tolerated, and c.377T > C, which is likely disruptive. This study highlights the potential underdiagnosis of B-cell lymphopenia caused by IGLL1 variants. Moreover, the comparison between clinically diagnosed cases and those identified through NBS underscores the importance of early diagnosis that facilitates close monitoring of affected patients from birth, timely initiation of immunoglobulin replacement therapy, and the prevention of complications and severe manifestations.